The effects of a 6-week pilates exercises on quality of life, depression, and musculoskeletal disorders in menopausal women - Arslan Kabasakal, Sema (The European Research Journal, 2025)
Objectives: This study examines the impact of a 6-week Pilates intervention on quality of life, depression, and musculoskeletal disorders in menopausal women. Methods: The sample comprised 13 menopausal women with a mean age of 59.45±11.52 years. Data collection was conducted using the World Health Organization Quality of Life-BREF (WHOQOL-BREF), the Beck Depression Inventory for Primary Care (BDI-PC), and the Cornell Musculoskeletal System Discomfort Questionnaire (CMSDQ). These instruments were administered at three intervals: baseline, following a 6-week non-intervention period, and after a subsequent 6-week Pilates program. Results: Within the scope of the study findings, after 6 weeks of Pilates, there was a significant increase in the participants’ quality of life scores in the physical and psychological health domains (p<0.05) and a significant decrease in the BDI-PC total score (p<0.05). However, no statistically significant difference was found in participants’ quality of life scores in the social relations and environmental health domains and the CMSDQ total weighted score after 6 weeks of Pilates (p>0.05). Conclusions: In conclusion, six weeks of Pilates exercises in menopausal women increases the quality of life within the framework of physical health and psychological health and reduces the depression level of these women. Therefore, to reduce the psychological problems that may occur in menopausal women and to improve their quality of life, they should be directed towards physical activities, especially Pilates. It is recommended to study the effect of Pilates performed for more than 6 weeks musculoskeletal disorders, environmental health and social relationships in this population.